The role of premorbid background in the clinical picture of acute respiratory viral infections in children - Toleukhankyzy , A.; Muti , M.M.; Baesheva , D.A.; Turdalina , B.R. (Eurasian Journal of Applied Biotechnology, 2025)
Background: To study the clinical features of the course of acute respiratory viral infections in children with a premorbid background. Materials and methods. A retrospective analysis of 125 medical histories of children diagnosed with acute respiratory viral infections who received inpatient treatment at the Children’s Infection Hospital in Astana during the period from 2023 to 2024. We conducted children with underlying diseases as a main group(I) and for the control group (II) - children without any other diseases. Results: Totally 125 patients were examined, of which 52.8% were children with underlying diseases and 47.2% without. The main symptoms in both groups were identified: cough (I gr.- 34.4%, II gr.- 37.6%), respiratory failure (I gr.- 28%, II gr.- 21.6%), convulsive syndrome (I gr.- 21.6%, II gr.- 10.4%) and dyspeptic syndrome (I gr.- 8.8%, II gr.- 5.6%). Cough was detected more in the control group compared to the main group, however the frequency of other symptoms was significantly higher in the I group than in the II group. A close relation can also be seen between the presence of cough and the subsequent development of respiratory failure (in 58.8% of both cases with cough eventually the respiratory failure was developed). Conclusion: In conclusion, patients with premorbid diseases due to their pre-infection health condition got more severe symptoms than the control group. Key words: ARVI, premorbid background, children, convulsions, dyspnea.